(3eQTO GdWdHI Edi EjVGM hLhg HYV BjGJ GdbQBf ef WQjb GdWjHIs - (3jhSa CeGe CafOj RGOg, CMeO QGTOs ((3YHO Gddg hMjOs)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdMeO dg hGdUdGI Ydi GdfHj (B: (3hHYO agPg QSGdI GdYHO CMeO QGTO GdYQja Hjf CbQGfg HjhSa CeGe CafOj RGOg aSCdfj hGdJeS Yfj (B( (3cPG (B) (3HYV ef GdWdHI GdQZHI Cf CMQQ QSGdI aj GdbQBf hSejJgG (B: (3eQTO GdWdHIs
(3BNQgG (B:s
(3hGdKGdK GdEScGf aj gG (B( (3jQg (B) (3ef caGjI CHj GdYR Yf GHf YHOGf Yf GdMdhGfj hgh WQjb GdOLhfj aj Yf gTGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs